Short Term Prognosis of Renal Artery Stenosis Secondary to Acute Type B Aortic Dissection With TEVAR - Li, Lei; Wang, Maozhou; Li, Jinzhang; Guan, Xinliang; Xin, Pu; Wang, Xiaolong; Liu, Yuyong; Li, Haiyang; Jiang, Wenjian; Gong, Ming; Zhang, Hongjia (Frontiers in Cardiovascular Medicine, 2021)
Objective: To determine the effect of renal artery stenosis (RAS) resulting from acute type B aortic dissection (ATBAD) with TEVAR on early prognosis in patients with ATBAD. Methods: A total of 129 ATBAD patients in the National Acute Aortic Syndrome Database (AASCN) who underwent thoracic endovascular aortic repair (TEVAR) between 2019 and 2020 were enrolled in our study. Patients were divided into two groups: the RAS group and the non-RAS group. Results: There were 21 RAS patients (16.3%) and 108 non-RAS patients (83.7%) in our cohort. No patient in our cohort died during the one-month follow-up. There was no significant difference in preoperative creatinine clearance rate (CCr) between the two groups (90.6± 46.1 µmol/L in the RAS group vs. 78.7± 39.2 µmol/L in the non-RAS group, P=0.303) but the RAS group had a significantly lower estimated glomerular filtration rate (eGFR) than the non-RAS group (83.3± 25.0 ml/min vs. 101.9 ± 26.9 ml/min, respectively; P=0.028).One month after TEVAR, CCr was significantly higher (99.0± 68.1 ml/min vs. 78.5 ± 25.8 ml/min, P=0.043) and eGFR (81.7 ± 23.8 ml/min vs. 96.0 ± 20.0 ml/min, P=0.017) was significantly lower in the RAS group than in the non-RAS group. Conclusions: In ATBAD, RAS could result in acute kidney injury (AKI) in the early stage after TEVAR. The RAS group had a high incidence of hypertension. These results suggest that patients with RAS may need further treatment.